Orphan love in the age of capital. Issue 1 (1st December 2016) - Skott-Myhre, Hans; Skott-Myhre, Kathleen; Kouri, Scott; Smith, Jeff
As we enter the second decade of the twenty-first century, who is to be served by institutions of care and to what ends becomes a pressing matter of concern. Foucault has suggested that the capitalist regime of rule in the twentieth century deployed residential settings as disciplinary apparatuses for shaping subjects to its colonial and industrial interests. However, in the twenty-first century, Deleuze has proposed that it is no longer discipline that is of primary concern for capitalism, but control through an ever-proliferating system of abstract code. It is within this context that terms, such as care within institutional residential encounters, open themselves to the necessity of interrogation. This paper will argue that residential care is a field of encounter saturated with a complex and intricate array of affects. If the rule of capitalism is designed to abstract lived experience, then any affirmation of the corporeal experience of encounter as lived experience might well constitute an alternative affirmation of life and hence a revolutionary set of possibilities. This paper will argue that it is love as creative desire that holds the most powerful possibilities for affirming the lived encounter to be found in residential care.